THE STUDY OF RAW WATER INTAKE AT SAGULING DAM FOR SOREANG BANJARAN REGIONAL UPSTREAM WATER SUPPLY SYSTEM DEVELOPMENT - CANDRA PURNAMA HADI NIM: 15313087, MOHAMAD
Regional Soreang Banjaran is a relatively developed area consisting of a number of districts of Bandung regency. This area is adjacent to Bandung, Cimahi, and Kota Baru Parahyangan in the north that tend to be more developed. The high growth rate of population of Regional Soreang Banjaran, which is an average of 2.3% during 2009-2015 (BPS Bandung Regency, 2016), encouraged decentralization of infrastructure development including drinking water infrastructure to the area. In order to achieve conceptual development concept, a competitive raw water source is needed to reach 100% drinking water service (SPAM). Saguling DAM has potential as a source of raw water SPAM Regional Soreang Banjaran located south of the reservoir. Research on Saguling DAM water source includes quantity & quality aspects. The design criteria required for drinking water quantity (DMI) is 10-20 years dry discharge ie at Saguling reservoir respectively 41.50 and 32.85 m3/s. This availability meets the raw drinking water requirements planned for phase I (2027) of 1,108 m3/s. The result of comparison of debit data and historical pollutant parameters of river and Saguling reservoir shows that there is no ideal condition of pollutant concentration as a function of water quantity which is inversely proportional. Thus the control of the polluted load on the waters has not run optimal. The result of Markov discrete stochastic simulation of river flow regime (quantity & quality) and water quality regime shows the value of correlation coefficient (r2) 0.21 and 0.18 respectively. Muara Ciminyak was chosen as the location of selected intake with water quality based on pollutant parameters that meet the class I water standard PP 82 year 2001. Upstream SPAM configurations planned in the form of floating intake (reservoir), intake pipes, pre-sedimentation basin, and transmission system with approximate plan budget of Rp 85,626,842,923. Based on NPV calculations, the project is economically feasible (NPV> 0).